Growth Response of Amorphophallus muelleri Blume Tuber to Etawa Goat Manure Fertilizer Application - Andi Masniawati (Jurnal Biologi Tropis, 2023)
Amorphophallus muelleri Blume, commonly known as Porang, is a glucomannan-producing plant with extensive benefits. To boost its production, proper fertilization methods are essential. However, excessive use of inorganic fertilizers can negatively impact soil fertility. Adopting environmentally friendly agriculture, this study explores the effect of etawa goat manure on the growth of Amorphophallus muelleri Blume tuber shoots. Conducted from September 2022 to February 2023, the research used a Completely Randomized Design with five treatments: P0 (control), P1 (100 g), P2 (200 g), P3 (300 g), and P4 (400 g), each replicated four times. Data analysis involved the SPSS 24.0 program, employing one way ANOVA test and 5% BNT test. Results indicated that etawa goat manure did not significantly affect sprouting age and shoot height, but significantly influenced shoot diameter of tubers. The most optimal dose was 400 g (P4), producing the highest average shoot height (5.61 cm) and shoot diameter (9.70 mm). The fastest sprouting age (7 days after planting) occurred with 200 g of manure (P2), while the slowest growth (31.50 days after planting) was observed in the 100 g dose treatment (P1). In conclusion, environmentally friendly practices, especially applying 400 g of etawa goat manure, enhance the growth of Amorphophallus muelleri Blume tuber shoots. These findings offer valuable insights into sustainable agricultural approaches to cultivate this valuable plant.